(untitled) (Journal of Economic Research & Business Administration, 2021)
The practice of only financial accounting-based reporting in the past is regarded as socially and environmentally unfriendly. This study, therefore, examines the impact of triple bottom line-based reporting on the accounting information disclosure of some selected money deposit banks in Nigeria. This study employed a survey research design. A sample of 300 staff of the selected banks were purposively selected from study population of eight selected banks in Nigeria. Primary data was collected through the questionnaire to elicit data from the respondents. The data collected was analyzed using correlation analysis, analysis of variances (ANOVA) and multiple regression models using SPSS version 20. The study found that the P-value of 0.00 < 0.01. Thus, TBL reporting has a positive effect on accounting information disclosure of banks in Nigeria. This study concluded that the activities of banks have moved beyond reporting only financial accounting information at the expense of accounting for social and environmental effects of these banks on the communities where they operate in Nigeria. This study recommends that the accountants should be financially motivated to acquire adequate knowledge on how to account for social and environmental activates of their companies. Key words: accounting information disclosure, banks, triple bottom-line.